Teachers' Secondment Experiences - Badali, Salvador J.; Housego, Billie E. (Alberta Journal of Educational Research, 2000)
This article explores seconded teachers' experiences as university instructors and faculty advisors in the Faculty of Education at the University of British Columbia. Data were collected in three one-hour semistructured interviews with each of the 17 participants. The purpose of the study was to understand more clearly the experiences of seconded teachers in the teacher education program through the use of Glaser and Strauss's (1967) grounded theory approach. Seven phases or aspects of secondment are outlined: seeking the position; preparing for secondment; expressing self-doubts; adjusting to the tempo and workload; working with adult learners; looking for support; and returning to the school community. Overall, the themes that emerged in this research highlight five central issues: the contrast between university and school cultures; the value of reflection on practice; the strength of seconded teachers' commitment to classroom teaching; the stability and nature of seconded teachers' professional identities; and the usefulness of secondment as professional development.